Tranformasi Sampah Plastic Menjadi Ecobrik Upaya Modern Menjaga Kelestarian Lingkungan - Nur Ramdani; Nur Mawar; St Dinar Sulistiya Ningrum; Riansyah Riansyah; Pipit Purwatiningsih; Novi Yanti Sandra Dewi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Plastic waste is an increasingly urgent environmental problem because it is difficult to decompose naturally and its amount continues to increase. This study aims to examine the transformation of plastic waste into ecobricks as a modern effort to preserve the environment, while also examining its social and economic benefits. The research method used was descriptive qualitative with the location in Pakuan Village, Narmada District, West Lombok. Data were obtained through observation, interviews, and documentation, then analysed through reduction, presentation, and conclusion drawing. The results showed that ecobricks were able to reduce the volume of household plastic waste that was previously scattered or burned. Community participation, especially among young people and children, is an important factor in the success of this programme because it encourages the growth of collective awareness. In addition, ecobricks have social benefits in the form of strengthening togetherness through mutual cooperation, as well as economic benefits as an alternative material that reduces the cost of simple construction. Thus, ecobricks are worthy of being developed as a sustainable solution in plastic waste management.